2009
DOI: 10.1002/nbm.1361
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of choline kinase activity in human cancer cells observed by dynamic 31P NMR

Abstract: Choline metabolites are widely studied in cancer research as biomarkers of malignancy and as indicators of therapeutic response. However, endogenous phosphocholine levels are determined by a number of processes that confound the interpretation of these measurements, including membrane transport rates and a series of enzyme catalysed reactions in the Kennedy pathway. Employing a dynamic (31)P NMR assay that is specific to choline kinase (ChoK) we have measured the rates of this enzyme reaction in cell lysates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Our MS imaging findings confirm the importance of PC in malignant tumor growth (23). Altered expression and activity levels of phosphatidylcholine metabolism-related enzymes, such as choline kinase (5, 8, 34), phospholipases C and D (42) and specific choline transporters (43) may account for the higher MS imaging-detected PC intensity in viable regions of the more aggressive tumor model. A recent studies in prostate tumor models detected increased tCho and PC concentrations in hypoxic tumor regions, and showed that hypoxia inducible factor-1 (HIF-1) signaling increased choline kinase expression, and hence PC production, under hypoxic conditions (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our MS imaging findings confirm the importance of PC in malignant tumor growth (23). Altered expression and activity levels of phosphatidylcholine metabolism-related enzymes, such as choline kinase (5, 8, 34), phospholipases C and D (42) and specific choline transporters (43) may account for the higher MS imaging-detected PC intensity in viable regions of the more aggressive tumor model. A recent studies in prostate tumor models detected increased tCho and PC concentrations in hypoxic tumor regions, and showed that hypoxia inducible factor-1 (HIF-1) signaling increased choline kinase expression, and hence PC production, under hypoxic conditions (3).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in activity and/or expression of several enzymes in choline metabolism, such as choline transporters (7), choline kinase (8), and phospholipases C (9) and D (10, 11) are responsible for the elevated PC and tCho concentrations in cancers, and provide potential therapeutic targets. Choline kinase has already been developed as a target for treatment (5, 12) and a predictive marker for cancer prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed to assay the total cellular activity of choline kinase as previously described [31], [32]. In brief, cell pellets (2×10 7 ) were resuspended in 540 µL lysis buffer containing 100 mM Tris-HCl (pH 8.0), 10 mM DTT and 1 mM EDTA in D 2 O. Lysate was homogenized on ice by repeated passage through fine-tipped needle (27G 1/2) and further disrupted by sonication 10×1s at 20 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…CHK activity was assayed using an MRS-based method as described [54], with modifications. Briefly, about 25 million cells were collected by trypsinization and washed in PBS.…”
Section: Chk Activity Assaymentioning
confidence: 99%